Design of amplifying information metasurface for enhancing signal coverage - Lijie WU; Hanqing YANG; Qiang CHENG; Tiejun CUI (Tongxin xuebao)
Traditional information metasurfaces can be used in wireless relay systems to control the propagation direction of electromagnetic waves due to their capability to control the amplitude and phase.However, owing to the lack of signal amplification function, these metasurfaces have a limited operating distance.Thus, a large size of metasurfaces is usually demanded to realize the signal coverage of dead zones.To solve this problem, an amplifying information metasurface was designed to realize the 2 bit phase manipulation and signal amplification function within the broad band from 2.7 to 3.1 GHz.Furthermore, a power dividing and combining network was introduced to combine the 1×8 metasurface elements into an array with only one amplifier, which greatly reduced the number of amplifiers, the hardware cost, and the power consumption.The simulation results indicate that the array can realize beamforming and signal amplification over a broad band.Therefore, the proposed amplifying information metasurface array may find important applications in wireless relay systems and provide a new solution to enhancing the signal coverage and reducing the size of the metasurface array.